Conversion of corn stover alkaline pre-treatment waste streams into biodiesel via Rhodococci. Issue 7 (13th January 2017) - Le, Rosemary K.; Wells Jr., Tyrone; Das, Parthapratim; Meng, Xianzhi; Stoklosa, Ryan J.; Bhalla, Aditya; Hodge, David B.; Yuan, Joshua S.; Ragauskas, Arthur J.
Abstract : The bioconversion of second-generation cellulosic ethanol waste streams into biodiesel via oleaginous bacteria, Rhodococcus, is a novel optimization strategy for biorefineries with substantial potential for rapid development. Abstract : The bioconversion of second-generation cellulosic ethanol waste streams into biodiesel via oleaginous bacteria is a novel optimization strategy for biorefineries with substantial potential for rapid development. In this study, one- and two-stage alkali/alkali-peroxide pretreatment waste streams of corn stover were separately implemented as feedstocks in 96 h batch reactor fermentations with wild-type Rhodococcus opacus PD 630, R. opacus DSM 1069, and R. jostii DSM 44719 T . Here we show using 31 P-NMR, HPAEC-PAD, and SEC analyses, that the more rigorous and chemically-efficient two-stage chemical pretreatment effluent provided higher concentrations of solubilized glucose and lower molecular weight (∼70–300 g mol −1 ) lignin degradation products thereby enabling improved cellular density, viability, and oleaginicity in each respective strain. The most significant yields were by R. opacus PD 630, which converted 6.2% of organic content with a maximal total lipid production of 1.3 g L −1 and accumulated 42.1% in oils based on cell dry weight after 48 h.